2012
DOI: 10.1111/j.1095-8312.2011.01838.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a mouth parasite in a marine fish differs between geographical areas

Abstract: Considerable variation exists in parasite virulence and host tolerance which may have a genetic and/or environmental basis. In this article, we study the effects of a striking, mouth-dwelling, blood-feeding isopod parasite (Ceratothoa italica) on the life history and physiological condition of two Mediterranean populations of the coastal fish, Lithognathus mormyrus. The growth and hepatosomatic index (HSI) of fish in a heavily human-exploited population were severely impacted by this parasite, whereas C. itali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 66 publications
1
16
0
1
Order By: Relevance
“…In the present study, some (not significant) tendency was observed between fish condition and parasite load among seasons. The negative relationship between high parasite loads (MSR) and condition of fish (HSI) in N. aequalis agrees with findings of several authors (Durieux et al, 2007;Lloret et al, 2012;Sala-Bozano et al, 2012), however, this trend is not always clearly evident or easy to identify (Lloret et al, 2012) as in the case of H. italicus and T. scabrus. By contrast, the relationship between the GSI and parasite load (MSR and MDI) tended to be positive in N. aequalis, in agreement with Abattouy et al (2011) who attributed it to a detrimental effect in immune defence.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, some (not significant) tendency was observed between fish condition and parasite load among seasons. The negative relationship between high parasite loads (MSR) and condition of fish (HSI) in N. aequalis agrees with findings of several authors (Durieux et al, 2007;Lloret et al, 2012;Sala-Bozano et al, 2012), however, this trend is not always clearly evident or easy to identify (Lloret et al, 2012) as in the case of H. italicus and T. scabrus. By contrast, the relationship between the GSI and parasite load (MSR and MDI) tended to be positive in N. aequalis, in agreement with Abattouy et al (2011) who attributed it to a detrimental effect in immune defence.…”
Section: Discussionsupporting
confidence: 88%
“…;Lafferty et al 2008b;Freeman and MacDiarmid, 2009;Ternengo et al 2009;Marzoug et al 2012;Sonnenholzner et al 2011;Sala-Bozano et al 2012;Wootton et al 2012;Wood et al 2013).…”
mentioning
confidence: 99%
“…However, microsatellite analyses did not detect spatial differentiation or differentiation according to host species, which points to random mating and high gene flow between parasitic crabs from the two hosts. A further study by Sala-Bozano et al (2012) applied microsatellites to investigate neutral genetic variation in an isopod mouth parasite (Ceratothoa italica) and its fish host, Lithognathus mormyrus. Here both host and parasite populations were not genetically differentiated and thus likely exchanged migrants.…”
Section: Microsatellitesmentioning
confidence: 99%